Seeking the imperishable treasure : wealth, wisdom, and a Jesus saying - Johnson, Steven R., 1961- (James Clarke & Co., 2010)
This book tracks the use of a single saying of Jesus over time and among theologically divergent authors and communities and identifies six different versions of the saying in the canonical gospels and epistles, as well as the Gospel of Thomas and Q. After tracing the tradition and redaction history of this wisdom admonition, the author observes at least two distinctly different wisdom themes that are applied to the saying: the proper disposition of wealth and the search for knowledge, wisdom, or God. What he discovers is a saying of Jesus with roots in Jewish wisdom and pietistic traditions,